# Solve for y 2(y-1)+8=6(2y-4) 2(y-1)+8=6(2y-4)
Simplify 2(y-1)+8.
Simplify each term.
Apply the distributive property.
2y+2⋅-1+8=6(2y-4)
Multiply 2 by -1.
2y-2+8=6(2y-4)
2y-2+8=6(2y-4)
Add -2 and 8.
2y+6=6(2y-4)
2y+6=6(2y-4)
Simplify 6(2y-4).
Apply the distributive property.
2y+6=6(2y)+6⋅-4
Multiply.
Multiply 2 by 6.
2y+6=12y+6⋅-4
Multiply 6 by -4.
2y+6=12y-24
2y+6=12y-24
2y+6=12y-24
Move all terms containing y to the left side of the equation.
Subtract 12y from both sides of the equation.
2y+6-12y=-24
Subtract 12y from 2y.
-10y+6=-24
-10y+6=-24
Move all terms not containing y to the right side of the equation.
Subtract 6 from both sides of the equation.
-10y=-24-6
Subtract 6 from -24.
-10y=-30
-10y=-30
Divide each term by -10 and simplify.
Divide each term in -10y=-30 by -10.
-10y-10=-30-10
Cancel the common factor of -10.
Cancel the common factor.
-10y-10=-30-10
Divide y by 1.
y=-30-10
y=-30-10
Divide -30 by -10.
y=3
y=3
Solve for y 2(y-1)+8=6(2y-4)

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top